KOMODIFIKASI PERAN BALIAN SEBAGAI THERAPIST SPIRITUAL DI FIVELEMENTS HOTEL, DESA MAMBAL, KECAMATAN ABIANSEMAL, KABUPATEN BADUNG - Putu Sabda Jayendra; I Wayan Restu Suarmana (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
The development of tourism and the hotel industry has implications for commodification. Basically, commodification is something that is modified so that it becomes of commodity value. One of these phenomena can be seen in the commodification of Balian's roles and functions at the Fivelements Hotel, which is located in Mambal Village, Abiansemal sub-district, Badung Regency. Balian is actually historically a profession that uses spiritual power to heal someone's illness. For the Balinese people, the Balinese profession is something magical, not just anyone can do it, and has high spirituality. Balian's profession and services are then used by Fivelements hotel to become one of the most iconic attractions. Fivelements Hotel, which is located at Mambal Village, Abiansemal District, Badung Regency, offers Balian services to its guests as healers or spiritual therapists. This phenomenon makes it something that is anti-mainstream and has essentially proven the commodification of its role. Moving on from this, this research analyzes the problem covering three things, namely; 1) the factors causing the commodification of the Balian role, 2) the forms of commodification of the Balian role as a spiritual therapist, and 3) the implications of the commodification of the Balian role as a spiritual therapist at Fivelements Hotel.Keyword : Balian, commodification, therapist, spiritual